Telesna nedejavnost, vsakodnevno dolgotrajno sedenje in nezdravo prehranjevanje - "kuge" 21. stoletja - Pinter, Stanislav (Šport (Ljubljana), 2016)
Physical inactivity, a prolonged sedentary lifestyle and unhealthy nutrition were identified a long time ago as the risk factors of excessive body weight and clinical obesity (hereinafter: obesity and the obese) as well as of a number of chronic diseases. How a modern person finds their way through this changed environment depends on a range of factors, mainly on the level of awareness about the many challenges that give rise to a need for an adjustment, the authenticity of the sources of information and the emerging possibilities and, eventually, the decisions to be made. The aim of the contribution is to provide accurate information about specific obsolete dogmas and to encourage the reader to take decisions that benefit their health.
Keywords: dolgotrajno sedenje; nezdravo prehranjevanje; physical inactivity; prolonged sedentary lifestyle; sport; šport; telesna nedejavnost; unhealthy nutrition; zdravo življenje